IMPLEMENTASI SISTEM INFORMASI KONSULTASI KEBUTUHAN GIZI PADA IBU HAMIL DENGAN METODE COOPER BERBASIS WEB PADA PUSKESMAS BUNGUS TELUK KABUNG PADANG - Putra, Hendra Nusa (Rang Teknik Journal, 2019)
This research was motivated by the problem of lack of knowledge and awareness of the nutritional needs of pregnant women during pregnancy at Bungus Teluk Kabung Padang Health Center. Pregnant women rarely do nutritional counseling to nutritionists about the diet and type of food that must be consumed during pregnancy because of limited time for consultation at Bungus Bay Kabung Health Center. Therefore nutritionists try to make the application of nutritional needs of pregnant women web-based with Cooper's method with the aim of making it easier for pregnant women to find information about nutritional intake through food menu selection. The Cooper method is a way of calculating the number of calories needed by a pregnant woman. The method used for system development is the system development life cycle method (SDLC), while the tools for modeling use UML (Unified Modeling Language). The programming language used for making this application is PHP and MySQL for the database. Based on this study, pregnant women can conduct online consultations as a means of providing solutions to find out the fulfillment of the nutritional needs of pregnant women and fetuses.